The impact of external academic accreditation of undergraduate medical program on students’ satisfaction - Ayman Al-Eyadhy (BMC, 2021)
Abstract Background The external academic accreditation is a quality assurance and auditing process that focuses on the structure, process, and outcome of the education. It is an interrupting and highly demanding process in terms of effort, time, financial, and human resources. However, it is unclear in the literature how much of these external quality assurance practices impeded in the accreditation processes would reflect on the other end of the learning pathway, including student satisfaction. Methods A retrospective quantitative secondary data analysis, with a before-after comparison research design, was performed to evaluate external accreditation’s impact on students’ mean satisfaction score within two accreditation cycles at King Saud University (KSU)-Bachelor of Medicine, Bachelor of Surgery (MBBS) program. Results The overall average students’ satisfaction scores pre-and-post the first accreditation cycle were 3.46/5 (±0.35), 3.71 (±0.39), respectively, with a P-value of < 0.001. The effect of post first accreditation cycle was sustainable for a couple of years, then maintained above the baseline of the pre-first accreditation cycle until the pre-second accreditation cycle. Similarly, the overall average students’ satisfaction scores pre-and-post the second accreditation cycles were 3.57/5 (±0.30) and 3.70 (±0.34), respectively, with a P-value of 0.04. Compared to the first accreditation cycle, the improvement of the mean score of students’ satisfaction rates was not sustained beyond the year corresponding to the post-second accreditation cycle. Conclusion Both accreditation cycles were associated with an increased score in students’ satisfaction. The preparatory phase activities and navigation through the self-study assessment while challenging the program’s competencies are essential triggers for quality improvement practices associated with accreditation.